Cretaceous sea-surface temperature evolution: Constraints from TEX86 and planktonic foraminiferal oxygen isotopes - O'Brien, C; Robinson, S; Pancost, R; Sinninghe Damsté, J; Schouten, S; Lunt, D; Alsenz, H; Bornemann, A; Bottinni, C; Brassell, S; Farnsworth, A; Forster, A; et al. (Elsevier, 2017)
It is well established that greenhouse conditions prevailed during the Cretaceous Period (~ 145–66 Ma). Determining the exact nature of the greenhouse-gas forcing, climatic warming and climate sensitivity remains, however, an active topic of research. Quantitative and qualitative geochemical and palaeontological proxies provide valuable observational constraints on Cretaceous climate. In particular, reconstructions of Cretaceous sea-surface temperatures (SSTs) have been revolutionised firstly by the recognition that clay-rich sequences can host exceptionally preserved planktonic foraminifera allowing for reliable oxygen-isotope analyses and, secondly by the development of the organic palaeothermometer TEX86, based on the distribution of marine archaeal membrane lipids. Here we provide a new compilation and synthesis of available planktonic foraminiferal δ18O (δ18Opl) and TEX86-SST proxy data for almost the entire Cretaceous Period. The compilation uses SSTs recalculated from published raw data, allowing examination of the sensitivity of each proxy to the calculation method (e.g., choice of calibration) and places all data on a common timescale. Overall, the compilation shows many similarities with trends present in individual records of Cretaceous climate change. For example, both SST proxies and benthic foraminiferal δ18O records indicate maximum warmth in the Cenomanian–Turonian interval. Our reconstruction of the evolution of latitudinal temperature gradients (low, <±30°, minus higher, >±48°, palaeolatitudes) reveals temporal changes. In the Valanginian–Aptian, the low-to-higher mid-latitudinal temperature gradient was weak (decreasing from ~ 10–17 °C in the Valanginian, to ~ 3–5 °C in the Aptian, based on TEX86-SSTs). In the Cenomanian–Santonian, reconstructed latitudinal temperature contrasts are also small relative to modern (< 14 °C, based on low-latitude TEX86 and δ18Opl SSTs minus higher latitude δ18Opl SSTs, compared with ~ 20 °C for the modern). In the mid-Campanian to end-Maastrichtian, latitudinal temperature gradients strengthened (~ 19–21 °C, based on low-latitude TEX86 and δ18Opl SSTs minus higher latitude δ18Opl SSTs), with cooling occurring at low-, middle- and higher palaeolatitude sites, implying global surface-ocean cooling and/or changes in ocean heat transport in the Late Cretaceous. These reconstructed long-term trends are resilient, regardless of the choice of proxy (TEX86 or δ18Opl) or calibration. This new Cretaceous SST synthesis provides an up-to-date target for modelling studies investigating the mechanics of extreme climates.